Special Drawing Rights (SDRs) and the COVID-19 crisis (United Nations, ECLAC, 2022)
The coronavirus disease (COVID-19) pandemic is the worst global crisis since the Second World War, with developing countries suffering more devastating economic and social effects than developed countries. Governments’ increased pandemic-related expenditure combined with the drastic fall in tax revenues have increased their fiscal deficits and heightened their debt vulnerabilities. The generalized increase in fiscal imbalances and indebtedness has given rise to greater liquidity needs across developing countries, despite considerable heterogeneity in their fiscal positions and debt profiles.Easing liquidity constraints and expanding fiscal space for all developing countries requires alternative mechanisms in addition to existing credit facilities. The new general allocation of US 650 billion in Special Drawing Rights (SDRs) implemented on 23 August 2021 provided the most expedient mechanism to provide concessional liquidity at scale to all countries regardless of their level of income. Aside from its agility and financial effects, SDRs are the only democratic device to enhance policy space in developing economies, as it comes with no conditionalities. „ SDRs have several advantages over other IMF credit facilities and financing lines, including the fact that they do not generate debt, have a very low cost of use, and can reduce the risk premium for highly indebted countries. The new issuance of SDRs can help boost the level of international reserves of developing economies, strengthen their external positions, reduce their liquidity and default risk, and free up resources to meet the Sustainable Development Goals (SDGs). Key messages .– A. The pandemic and developing countries’ financing needs .– B. SDRs and their advantages .– C. Recipient countries ofthe SDR allocation .– D. Determining the value of SDRs to be reallocated from developedto developing countries (low-and middle-income countries) .– E. Proposed means of reallocating SDRs .– F. Conclusion.
11362/47856
Keywords: Graue Literatur; Amtliche Publikation; financing for development; fiscal affairs; foreign exchange; monetary reserves; capital markets; developed countries; development finance; viruses; economic aspects; fiscal policy; macroeconomics; epidemics; DIVISAS; RESERVAS MONETARIAS; MERCADOS DE CAPITAL; PAISES DESARROLLADOS; PAISES EN DESARROLLO; FINANCIACION DEL DESARROLLO; COVID-19; VIRUS; EPIDEMIAS; ASPECTOS ECONOMICOS; POLITICA FISCAL; MACROECONOMIA; FOREIGN EXCHANGE; MONETARY RESERVES; CAPITAL MARKETS; DEVELOPED COUNTRIES; DEVELOPING COUNTRIES; DEVELOPMENT FINANCE; VIRUSES; ECONOMIC ASPECTS; FISCAL POLICY; MACROECONOMICS